ANALISIS STUDI KELAYAKAN BISNIS PADA PANGKALAN GAS LPG “RANA” DI DESA CIBATU KECAMATAN CIKARANG SELATAN KABUPATEN BEKASI (Ditinjau dari Aspek Teknis, Aspek Pasar dan Pemasaran, dan Aspek Keuangan) - Retna Widianingsih; R.R Wening Ken Widodasih; Kurbandi Satpatmantya BR (LPPM Institut Pendidikan Nusantara Global, 2023)
In Indonesia, the use of gas is a more economical alternative, one example is the conversion of kerosene to 3kg LPG. According to BPS statistical data, the use of LPG in Indonesia exceeds 83.36% of households using LPG for cooking. The purpose of this study is to assess the business feasibility of the